Gender and innovation for climate-smart agriculture. Assessment of gender-responsiveness of RAN's agricultural-focused innovations - Okello, Dorothy; Mayega, Roy William; Muhumuza, Christine; Amuge, Peace Oliver; Kakamagi, Edna; Amollo, Matthew; Amuka, Isaac; Kayiwa, Ronald; Bazeyo, William (2018)
Ownership of agricultural production resources has generally been shown by research to be male dominated and to have wide disparities between males and females. The disparities are more pronounced in rural areas where women have less income, smaller pieces of land, and have inadequate market for their produce. In dealing with Climate Smart Agriculture (CSA) adoption and with agricultural technology adoption, there has been increasing recognition of the importance of focusing on the gender-based needs behind the adoption choice itself. Grounded in the belief that solutions to Africa’s resilience challenges lie in understanding what makes communities thrive in adversity, ResilientAfrica Network (RAN) is a multidisciplinary innovation lab that leverages the creativity and talent of youth, students, scholars and communities to develop and scale innovative ideas. Given how dominant agriculture is among RAN's problem sets for strengthening resilience through innovation, RAN sought to understand how supported innovations had contributed to gender-responsive climate smart agriculture solutions. What lessons could be learned from Women of Uganda Network (WOUGNET) in their history of engagement with women farmers to co-create a gender-responsive innovation process to strengthen resilience through the agricultural sector? With the support of CCAFS, RAN and WOUGNET conducted a gender assessment exercise to evaluate if the current solutions/innovations are gender responsive or not. Three innovations were selected that are primarily focused towards CSA and that had affordability and ease of use as key objectives. The gender assessment embraced a qualitative research approach. This choice was guided by the need to appreciate respondents’ understanding and experiences or perceptions of the different innovations that RAN has been nurturing and developing over the years. The respondents were purposively selected based on availability and on being located in any of the four Northern Uganda districts of Apac, Kole, Lira and Oyam where WOUGNET has actively engaged with women farmers. From the study, it was clear that men and women farmers are willing to embrace new technologies, practices and innovations in their pursuit of enhanced agricultural productivity and new opportunities. That said, a clearly gendered view emerged from the assessment in that uptake of the innovations was to a large extent driven by socio-cultural norms and expectations related to issues of ownership, work, decision making capacity, and income generation and control. For instance, use of the innovations can reduce time spent on farming activities and can open up time and space to explore new opportunities. However, if gender considerations are not taken into account, such time could be used to negatively impact on the work burden for women farmers as it may be taken that the women are now free to take on new work – even that which would have been previously done by the men in their households.